ÐÐ½Ð°Ð»Ð¸Ð· ÑÐ¾ÑÑ‚Ð¾ÑÐ½Ð¸Ñ ÐºÐ»ÐµÑ‚Ð¾Ñ‡Ð½Ñ‹Ñ… ÐºÑƒÐ»ÑŒÑ‚ÑƒÑ€ Ð¿Ð¾ÑÐ»Ðµ ÐºÑ€Ð¸Ð¾ÐºÐ¾Ð½ÑÐµÑ€Ð²Ð¸Ñ€Ð¾Ð²Ð°Ð½Ð¸Ñ Ñ Ð¸ÑÐ¿Ð¾Ð»ÑŒÐ·Ð¾Ð²Ð°Ð½Ð¸ÐµÐ¼ Ñ„Ð»ÑƒÐ¾Ñ€ÐµÑÑ†ÐµÐ½Ñ‚Ð½Ñ‹Ñ… Ð·Ð¾Ð½Ð´Ð¾Ð² - Onischenko, E. V.; Goncharuk, E. I.; Petrenko, T. F.; Borovoy, I. A.; Malyukin, Yu. V.; Grischenko, V. I. (Publishing House ‘Akademperiodyka’ of the National Academy of Sciences of Ukraine; Institute for Problems of Cryobiology and Cryomedicine, 2008)
Interaction of fluorescent probes of different structures with cultured cells prior to and after cryopreservation were investigated. It has been noted that optimal dyes for monitoring of functional state of cells after cryo-effect are the probes of carbocyanine series.